2010
DOI: 10.1097/bsd.0b013e3181bf99c6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Low Back Pain in Adolescents

Abstract: Systematic physical activity and control of psychological profile should decrease LBP frequency and intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 68 publications
1
12
0
1
Order By: Relevance
“…Korovessis et al (6) revealed that the factor of gender was against the females for the severity and frequency of low back pain and that there was a relationship between physical activity and low back pain. Consistent with literature, the incidence and severity of low back pain were higher in female students (91.3% and 3.7±1.9, respectively) than in male students in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korovessis et al (6) revealed that the factor of gender was against the females for the severity and frequency of low back pain and that there was a relationship between physical activity and low back pain. Consistent with literature, the incidence and severity of low back pain were higher in female students (91.3% and 3.7±1.9, respectively) than in male students in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, it is seen that most studies on low back pain have been conducted on adolescents or female students (2,6). There are also some studies on low back pain among students studying at other faculties such as engineering and education (2,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant association between anxiety and pain report in men but not in women. However, among women, depression, catastrophizing, anxiety sensitivity, stress, low energy and pain reports were significantly associated (Korovessis, 2010;Robinson et al, 2005).…”
Section: Psychological/emotional Distressmentioning
confidence: 99%
“…The most common prevalence periods were 1-month (22 studies) [8,, 6-months (7 studies) [34,[42][43][44][45][46][47], followed by 3-months [48][49][50][51] and 1-year prevalence [9,31,34,52] with four studies each. Table 1 summarizes the characteristics of the included studies (author/year, study design, sample characteristics, the pain definition used and measuring tools).…”
Section: Study Characteristicsmentioning
confidence: 99%